A marginalização da pessoa com deficiência e os discursos e práticas cristãs - Ribeiro, Sheila Santos Carvalho (2019)
The object of this study is the Christian religious phenomenon as a space of discourses and practices that legitimize the marginalization of the disabled person. The general objective is to analyze the occurrences of the marginalization of the person with disabilities through Christian discourses and practices. The specific objectives are to understand the approximations and distances of the inclusive religious discourses and practices of Christianity in relation to the disabled person, to investigate the elements that underlie the Christian discourse regarding the disabled person and the religious intentionality regarding inclusion and to observe the various religious significations of the empirical field in relation to the way of perceiving the person with disability and to channel their marginalization. The methodology adopted is discourse analysis, through the theoretical resources and the observations of the empirical field. The hypothesis comes from the analysis that the marginalization is marked by the culture of exclusion, directly linked to lack of information, prejudice and indifference. The research is justified by the occurrences of the marginalization of the disabled person, which generate worries in the social context. The religious implications of exclusion demonstrate symbolic and practical power, whose marginalization also occurs because of the limited discussion on the subject. The three chapters present approximations and distances of the Christian religion and its ethos in the society, as far as the conceptions of body and deficiency; the intentionality of religion, against the marginalization of persons with disabilities; the Christian context, from the empirical field of twelve religious institutions, which include inclusion and/or exclusion. The results indicate that the continuity of marginalization prevails, and it is necessary to disrupt discourses and practices, to recognize the rights of people with disabilities, and the principle of equality to the detriment of a hegemonic perspective of charity and piety.